Correlation of patellofemoral joint morphology with the size of chondromalacia patella based on MRI examination - Ismiyati, Galih Nur; Rahardjo, Paulus; Setiawati, Rosy (Edelweiss Applied Science and Technology, 2024)
Determine correlation between patellofemoral joint morphology and chondromalacia patella (CMP) size based on magnetic resonance imaging (MRI) examination. This study is an analytical observational study with retrospective approach. The sample consisted of patients aged 10-50 who underwent knee MRI. We evaluated patellofemoral morphological variables and compared them with the results of size CMP lesions. The total sample size was 63, comprising 47 samples that exhibited chondromalacia patella (CMP) and 16 samples without CMP. Significant correlations (p < 0.05) were observed between the trochlear sulcus angle (TSA), trochlear depth (TD), and lateral trochlear inclination (LTI) with the size of CMP. Specifically, a larger TSA angle was associated with a greater size of CMP, while smaller TD and LTI angles correlated with a larger size of CMP. In contrast, the patella-patellar tendon angle (PPTA), patella type, and Insall-Salvati ratio did not demonstrate any correlation (p > 0.05) with the size of CMP. There is a correlation between TSA, TD, and LTI with the size of CMP. No correlation was found between PPTA, patella type, and Insall-Salvati ratio with the size of CMP.